Nonclinical safety assessment of SPX-101, a novel peptide promoter of epithelial sodium channel internalization for the treatment of cystic fibrosis. (3rd July 2017) - Walker, Matthew P.; Cowlen, Matt; Christensen, Dale; Miyamoto, Mutsumi; Barley, Phillip; Crowder, Timothy
Abstract: Background: ENaC inhibition has long been an attractive therapeutic target for the treatment of cystic fibrosis. However, previous attempts at developing ENaC inhibitors have been unsuccessful due to complications arising from systemic circulation of the compounds. Here, we describe the preclinical toxicology assessment of a new inhaled peptide promoter of ENaC internalization delivered as a nebulized aerosol. Methods: Preclinical assessment of SPX-101 safety was determined using an in vitro hERG assay, bolus injection of SPX-101 in a canine cardiovascular and respiratory safety pharmacology model and 28-day inhalation toxicology studies of nebulized drug in rats and dogs. Results: SPX101 had no effects on the respiratory, cardiac or central nervous systems. The 28-day inhalation toxicology studies of nebulized SPX-101 in rats and dogs revealed no drug-related adverse events. Plasma levels of SPX-101 peaked less than 1 h after the end of treatment in rats and were below the limit of detection in canine models. Conclusions: SPX-101, a novel peptide promoter of ENaC internalization, elicited no adverse effects at doses up to the MFD and in excess of the highest preclinical efficacious and expected clinical doses. In contrast to channel blockers like amiloride and derivative small molecules, SPX-101 does not achieve significant systemic circulation, thus doses are not limited due to toxic side effects like hyperkalemia and weight loss.